ANALISIS PERTUMBUHAN PAJAK DAERAH SEBAGAI SALAH SATU PEMASUKAN PENDAPATAN ASLI DAERAH (PAD) KOTA MAGELANG - AMRINA MAULIDA; RISMA WIRA BHARATA (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
This study aims to measure the local taxes of the City of Magelang in 2019 compared to the previous year. The type of data used in this research is quantitative data in the form of detailed data on Magelang City revenue in 2017-2019. Sources of data used in this study are secondary data, in the form of data on Magelang City Revenue realization from 2017-2019 which were obtained from the BPKAD office of Magelang City. The results of this study indicate that the regional tax growth ratio of the City of Magelang has increased every year. In 2017, the City of Magelang Regional Tax increased by 2%. Then in 2018 the Regional Tax of the City of Magelang increased by 9.8% and in 2019 the Regional Tax of the City of Magelang increased by 17.9%. The increase in regional taxes in the City of Magelang also affects the total Regional Original Income (PAD) which automatically increases every year. This shows that the City of Magelang has been independent in building and increasing regional income, especially in the tax section.